Деякі результати досліджень поселення черняхівської культури біля с. Новоберецьке - Мизгін, К.В. (Археологія, 2011)
Розглянуто залишки двох наземних глинобитних споруд, досліджених у 2008—2010 рр. на поселенні біля с. Новоберецьке, що становлять інтерес для вивчення будівельних традицій черняхівського населення північно-східного ареалу культури. Освещены результаты исследования поселения черняховской культуры возле с. Новоберекское Первомайского р-на Харьковской обл. в 2008—2010 гг. Памятник расположен на западном, северном и южном склонах балки, по дну которой протекала речка четвертого порядка донской системы. На сегодняшний день поселение является наиболее южным известным в регионе черняховским памятником. Его площадь (16—18 га) условно делится на два участка: А и Б. Изучению подвергался только участок А. Стратиграфические условия поселения определили хорошую сохранность его культурного слоя. На площади раскопа І исследованы остатки двух наземных объектов и две хозяйственные ямы. Находки на поверхности поселения и в его слое представлены фрагментами гончарной, реже — лепной керамики, фрагментами амфор типа Шелов F, изделиями из глины (фрагменты грузил, пряслице, бусина), камня (фрагменты точильных камней), стекла (бусы), железа (нож, части шильев и проч.) и серебра (височное кольцо). Изученные объекты являются остатками двух наземных глинобитных сооружений. Исследование их обмазки позволило выделить три группы отпечатков деревянных частей: прутья, жерди и столбы. Если основную часть отпечатков объекта 1 составляют жерди, то в объекте 2 таковыми являються прутья. Сравнительный анализ отпечатков обмазки из двух объектов свидетельствует о значительной близости конструкции строений. Определение хронологии поселения затруднено из-за отсутствия хроноиндикаторов с «узкими» датами. Амфорный материал и бусы, обнаруженные на памятнике, позволяют отнести существование поселения к IV — началу V вв. Described are the results of research of the Chernyakhiv culture settlement near Novoberetske Village of Pervomaysk Region in Kharkiv Oblast in 2008—2010. The site is situated on the western, northern, and southern slopes of a gully, in the bottom of which a river of the fourth order of the Don system flowed. The settlement is the most south Chernyakhiv culture site in the region today. Its territory (16—18 hectares) is conventionally divided into two areas: A and B. Only the area A was studied. Due to the site’s stratigraphic conditions its cultural layer is well preserved. The remains of two overland structures and two husbandry pits were studied at the area of excavation trench I. Finds on the surface of settlement and in its layer are represented by fragments of wheel-turned, or more rarely of hand-made, pottery, fragments of Shelov F type amphorae, earthenware (fragments of sinkers, a spindle whorl, a bead), stoneware (fragments of grindstones), glassware (beads), ironware (a knife, awls fragments, etc.), and silverware (temporal ring). Objects studied are the remains of two overland structures with cob walls. Research of their plastering allowed the author to define three groups of imprints of wooden elements: twigs, poles, and slabs. While poles are the main part of imprints in the object 1, poles are such in the object 2. The comparative analysis of plastering imprints from the two objects shows a significant closeness of the buildings’ structures. Defining the settlement chronology is complicated because of the absence of chronological indications with «narrow» dates. Amphorae material and beads found at the site make it possible to date the settlement by the 4th c. and the beginning of the 5th c.